Niobium carbide–mediated photothermal therapy for infected wound treatment - Ren, Junyu; Da, Junlong; Wu, Wei; Zheng, Ce; Hu, Narisu (Frontiers in Bioengineering and Biotechnology, 2022)
Bacterial infections of the wounds on the skin surface significantly reduce the rate of wound healing, potentially leading to serious systemic infections. Antibiotics are the first-line drugs for the treatment of these infections. However, the misuse and overuse of antibiotics have led to the emergence of bacterial resistance. Therefore, a new antimicrobial strategy is urgently needed. Photothermal therapy (PTT) is a novel efficient therapeutic technique that can produce irreversible cell damage to induce death of bacteria, possessing a great potential in infected wound healing. This work describes the use of a new photothermal agent (PTA) such as niobium carbide (NbC) nanoparticles with outstanding near-infrared (NIR) absorption property. NbC nanoparticles converted NIR laser irradiation energy into localized heat for photothermal treatment. In vitro antimicrobial experiments have revealed that NbC nanoparticles exert excellent antimicrobial effects against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). Moreover, NbC nanoparticles accelerated E. coli–infected wound healing process, reduced inflammatory response, and showed good biosafety in vivo. Altogether, NbC nanoparticles represent an efficient PTA for antimicrobial treatment and are a bio-safe material with low toxicity in vivo.